Production, optimization and characterization of polylactic acid microparticles using electrospray with porous structure - Tasci, M.E.; Dede, B.; Tabak, E.; Gur, A.; Sulutas, R.B.; Cesur, S.; Ilhan, E.; Lin, C.-C; Paik, P.; Ficai, D.; Ficai, A.; Gunduz, O. (MDPI AG, 2021)
Polymeric microparticles with controlled morphologies and sizes are being studied by researchers in many applications, such as for drug release, healthcare and cosmetics. Herein, spherical and porous polymeric microparticles of different sizes and morphologies by electrospray technique have been developed as a viable alternative. In this work, polylactic acid (PLA) microparticles with a spherical shape and porous morphology were successfully produced via an electrospray technique in a single step. Molecular interactions between the components and the effect of parameters, such as varying solvent compositions, flow rates and voltage on microparticle morphology, were investigated over the particle formation. It was observed that the type of solvents used is the most effective parameter in terms of particle morphology, size and distribution. When the optical microscopy and SEM images of the microparticles were examined, 3 wt.% PLA in dichloromethane (DCM) solution concentration with an applied voltage of 18 kV and a flow rate of 20 µL/min was found to be the optimum parameter combination to achieve the desired spherical and porous micron-size particles. The average diameter of the particles achieved was 3.01 ± 0.58 µm. DCM was found to be a more suitable solvent for obtaining microparticles compared to the other solvents used. Finally, particles that are obtained by electrospraying of PLA–DCM solution are porous and monodisperse. They might have excellent potential as a carrier of drugs to the targeted sides and can be used in different biomedical applications. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: electrospraying; porous microparticle; optimum size; polylactic acid (PLA); morphology